Shared Emotions in Music - Cochrane, Thomas (2007)
In this thesis I show that groups can share token emotional states by performing music together. First I argue that emotions are perceptions, representing the self's dynamic relation with the world. This representation is achieved by patterns of bodily changes, functioning independently of conscious feeling. Moreover, emotional expressions should be included in this analysis because they contribute to the pattern of bodily changes. This entails that we can 'think through' our emotions by manipulating our behavioural expressions. I then argue that empathy relies on our tendency to neurally mirror the expressive behaviours of other people, resulting in a simulation of emotional arousal.